(untitled) (Ukrainian Journal of Ophthalmology, 2025)
The effectiveness of trabeculoplasmy in lowering intraocular pressure (IOP) in glaucoma patients was determined. A longitudinal study was carried out in 10 patients with open-angle glaucoma that underwent trabeculoplasmy. The postoperative results Of IOP, visual acuity (VA) and the occurrence of complications were evaluated at 24 hours, one week, 3, 6, 9 and 12 months. 10 surgeries were performed (10 eyes, 10 patients). Preoperative average IOP was 32.5mmHg and preoperative VA was 0.5. At one year the average IOP was 10.10 mmHg and the average VA was 0.7, both values were significant (p<0.001, p=0.019 respectively). Trabeculoplasmy may be effective technique in the treatment of glaucoma, providing a decrease and maintenance of IOP within normal limits after one year of follow-up.